Observation of single-spin transport in an island-shaped CoFeB double magnetic tunnel junction prepared by magnetron sputtering. Issue 4 (1st February 2016) - Siripongsakul, Thamrongsin; Naganuma, Hiroshi; Kovacs, Andras; Kohn, Amit; Oogane, Mikihiko; Ando, Yasuo
Abstract: The Co40 Fe40 B20 (CFB)/MgO/CFB/MgO/CFB-based multilayer was prepared by conventional magnetron sputtering and utilised in the fabrication of double magnetic tunnel junctions (DMTJs) for which the middle CFB layers were island-shaped. By analysing the magnetic property of the CFB islands with Langevin's equation, it was possible to identify their diameters of 7.6, 8.9 and 11.0 nm; accordingly submicron-scaled DMTJs were fabricated to investigate single-spin transport phenomena. The coulomb staircase and the oscillatory tunnel magnetoresistive (TMR) were able to be observed at 6 K, where the TMR ratio was enhanced up to 60%, which is the highest value ever achieved in this structure.